No Use : Nuclear Weapons and U.S. National Security - Nichols, Thomas M., 1960- (Book collections on Project MUSE., 2014)
In No Use, national security scholar Thomas M. Nichols examines the role of nuclear weapons and their prominence in U.S. security strategy, ultimately arguing that this belief in the utility of nuclear force is misguided and dangerously obsolete.